Pengaruh Penerapan Strategi Kreatif-Produktif Terhadap Pemahaman Konsep Matematis Siswa Kelas VII SMPN 2 Dua Koto Kabupaten Pasaman Tahun Pelajaran 2012-2013, Skripsi, Program Studi Pendidikan Matematika, STKIP PGRI Sumatera Barat, Padang, 2013. - Maiyarsi, Eti; Rismen, Sefna; Haryono, Yulia (Pendidikan Matematika, 2013)
This research is motivated by the lack of understanding of mathematical concepts and students lack of confidence in his opinion. This study aims to determine how the activity and mathematical concepts student with the application of creative - productive strategy better than the students understanding of mathematical concepts with conventional learning students SMPN 2 Dua class VII Koto Pasaman. This type of research is the design of experimental studies Random Subjects . The population in this study were all students of class VII SMPN 2 Dua Koto Pasaman academic year 2012/2013. Than VII.2 class selected as the experimental class and the control class VII.3 . This research instrument is the final test in the form of essay. Data were analysis with a normality test , homogeneity test and t-test. Based on the analysis of data obtained by the average percentage of student activity during the learning process is increasing and the average results of tests students understanding of mathematical concepts experimental class was 79.48 better than the control class is 35.43 . Hypothesis testing using parties with the help of MINITAB, obtained P -value of 0.000 is smaller than a = 0.05 , so it can be concluded that the students understanding of mathematical concepts by applying creative - productive strategy is better than the students understanding of mathematical concepts conventional teaching class VII SMPN 2 Dua Koto Pasaman.